Spinal Deformity A Case-Based Approach to Managing and Avoiding Complications (Springer International Publishing, 2018)
Although there are a number of excellent books dedicated to spinal deformities, this text employs a case-based format which offers the advantage of easy readability. This format will allow the reader to better synthesize the dense information encompassing spinal deformity complications and pearls to avoid them. Example cases highlight the importance of appropriate diagnosis, radiographic assessment, classification, surgical decision making, and complication avoidance. In addition, complication management is emphasized since complications will occur regardless of skill level, experience, or meticulous technique given the complex nature of spinal deformity. Written by key thought leaders, this book not only provides state of the art concepts and techniques but also provides pearls and tips to manage and avoid complications. This book will be useful to the spinal surgeon of any experience level who is interested in optimizing their care for patients with symptomatic spinal deformity. In addition, the concepts presented in this text will be valuable to residents and fellows training in spinal surgery.